Enantioselective toxic effects of cyproconazole enantiomers against Chlorella pyrenoidosa. (September 2016) - Zhang, Wenjun; Cheng, Cheng; Chen, Li; Di, Shanshan; Liu, Chunxiao; Diao, Jinling; Zhou, Zhiqiang
Abstract: Enantioselectivity in ecotoxicity, digestion and uptake of chiral pesticide cyproconazole to Chlorella pyrenoidosa was studied. The 96h-EC50 values of rac- and the four enantiomers were 9.005, 6.616, 8.311, 4.290 and 9.410 mg/L, respectively. At the concentrations of 8 mg/L and 14 mg/L, the contents of pigments exposed in rac-, enantiomer-2 and 4 were higher than that exposed in enantiomer-1 and 3. The superoxide dismutase (SOD) and catalase (CAT) activity of algae exposed to enantiomer-1 and 3 was higher than that exposed to the rac-, enantiomer-2 and 4 at three levels. In addition, the malondialdehyde (MDA) concentrations in algae disposed with enantiomer-1 and 3 were increased remarkably at three levels. For the digestion experiment, the half-lives of four enantiomers in algae suspension were 28.06, 19.10, 21.13, 15.17 days, respectively. During the uptake experiment, the order of the concentrations of cyproconazole in algae cells was enantiomer-4, 2, 3 and 1. Based on these data, we concluded that ecotoxicity, digestion and uptake of chiral pesticide cyproconazole to C. pyrenoidosa were enantioselective, and such enantiomeric differences must be taken into consideration when assessing the risk of cyproconazole to environment. Graphical abstract: Highlights: The acute toxicity of cyproconazole against Chlorella pyrenoidosa was enantioselective. Some biomarkers of four cyproconazole enantiomers to algae were different. Enantioselective biodegradation occurred in the algae exposed to racemate. There was enantioselective bioaccumulation in the rac-treated algae.